Academic Integrity Policies in HEIs Across Cultures - Yankova, Diana (English Studies at NBU, 2024)
Academic integrity is a cornerstone of higher education, ensuring that students engage in honest and ethical practices in their pursuit of knowledge. The implementation of academic integrity policies varies across countries, reflecting the unique cultural, societal, and educational contexts of each nation. This article compares academic integrity policies in New Zealand, Australia, and Canada to those in Bulgaria, highlighting the similarities and differences that exist between these diverse educational landscapes. The study applies the well-known methodology by Bretag et al. (2011) whereby an exemplary academic integrity model is evaluated on the basis of five components, namely access, approach, responsibility, detail and support. This methodology is enriched by a modification suggested by Perkins and Roe (2023) in which a sixth component is added – technological explicitness, which involves the necessity to include and constantly update information and provide guidelines about new technologies.